2013
DOI: 10.1002/mds.25541
|View full text |Cite
|
Sign up to set email alerts
|

Mild cognitive impairment in patients with Parkinson's disease is associated with increased cortical degeneration

Abstract: Mild cognitive impairment (MCI) can occur early in the course of Parkinson's disease (PD), and its presence increases the risk of developing dementia. Determining the cortical changes associated with MCI in PD, thus, may be useful in predicting the future development of dementia. To address this objective, 37 patients with PD, divided into 2 groups according to the presence or absence MCI (18 with and 19 without) and 16 matched controls, underwent anatomic magnetic resonance imaging. Corticometry analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 56 publications
(100 reference statements)
7
42
0
Order By: Relevance
“…Thus, early identification of MCI among PD patients is of clinical importance in order to retard progression to PDD. Neuroimaging studies have indicated alterations in widespread cortical regions among PD-MCIs, compared to healthy controls [8,9], though some have reported negative findings [6,10]. Compared with cognitively asymptomatic PD patients, our previous work [11] and the work of others have revealed reduced gray matter (GM) volume in PD-MCI [3,12], especially in the frontal and subcortical regions, supporting the frontostriatal dysfunctional theory for cognitive impairment in PD.…”
Section: Introductionmentioning
confidence: 67%
“…Thus, early identification of MCI among PD patients is of clinical importance in order to retard progression to PDD. Neuroimaging studies have indicated alterations in widespread cortical regions among PD-MCIs, compared to healthy controls [8,9], though some have reported negative findings [6,10]. Compared with cognitively asymptomatic PD patients, our previous work [11] and the work of others have revealed reduced gray matter (GM) volume in PD-MCI [3,12], especially in the frontal and subcortical regions, supporting the frontostriatal dysfunctional theory for cognitive impairment in PD.…”
Section: Introductionmentioning
confidence: 67%
“…A few studies consistently showed that PD with MCI may be associated with gray matter atrophy in limited regions of frontal and temporal regions (Hanganu et al 2013;Melzer et al 2012;Song et al 2011) while one of them additionally showed parietal volume loss (Melzer et al 2012) and others, occipital volume loss (Hanganu et al 2013;Song et al 2011). A longitudinal study also demonstrated higher rates of cortical thinning in the frontal and temporal regions, extending to parietal cortex .…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, non-demented PD patients show faster progression of gray matter changes including atrophy and cortical thinning than healthy controls (HCs) in diffuse areas including frontal, temporal and parietal regions (Hu et al 2001;Ibarretxe-Bilbao et al 2012), restricted regions to cortical motor areas and cerebellum (Ibarretxe-Bilbao et al 2010), or limbic, paralimbic, and temporo-occipital regions (Ramirez-Ruiz et al 2007). Among PD patients, variability in cortical thickness and/or subcortical volume is also associated with cognitive measures (Biundo et al 2011;Camicioli et al 2009;IbarretxeBilbao et al 2009;Melzer et al 2012;Pellicano et al 2012;Zarei et al 2013), facial emotion recognition , duration of disease (Hanganu et al 2013;Jubault et al 2011;Lyoo et al 2011), motor severity (Lyoo et al 2011;Melzer et al 2012;Zarei et al 2013) and stage (Zarei et al 2013) as well as dopamine (DA) non-responsive symptoms (Brenneis et al 2003;Camicioli et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the risk score for PD patients could be a neuropsychological biomarker integrating the dementia-predicting values of various neuropsychological tests. Considering that cortical thickness in PD patients has a significant correlation with general cognition and could reflect structural changes from cognitively normal PD to PD dementia (PDD) [12,13], finding cortical regions that are related to the cognitive risk score in nondemented PD patients could reveal the most important brain region for future dementia progression in PD patients.…”
Section: Introductionmentioning
confidence: 99%